Evidence revealing the role of T cell regulators (Tregs) in periodontal diseases: A review - Paavai Ilango; Dhanapriya Kumar; Arulpari Mahalingam; Abirami Thanigaimalai; Vineela Katam Reddy (Wolters Kluwer Medknow Publications, 2021)
Periodontitis is an inflammatory disease of the periodontium, which is a reflection of the overgrowth of oral commensals. This alteration in the oral microbiota initiates inflammation of the gingiva, which when left untreated, terminates with the resorption of the alveolar bone that may lead to a poor and hopeless prognosis. With upcoming trends in modulating the host's immunity, the role of regulatory T-cells has gained importance. These T-cells defend against inflammation and autoimmunity as they suppress both. However, in both the conditions, the regulatory cells are invariably reduced in number. Novel methods to enhance the function of Tregs have made their way in dentistry, as a promising approach to cure periodontitis. This article discusses various significant tests and trials of Tregs in the recent years.